Elevated blood purine levels as a biomarker of seizures and epilepsy. (18th February 2021) - Beamer, Edward; Lacey, Austin; Alves, Mariana; Conte, Giorgia; Tian, Faming; de Diego‐Garcia, Laura; Khalil, Mohamed; Rosenow, Felix; Delanty, Norman; Dale, Nicholas; El‐Naggar, Hany; Henshall, David C.; et al.
Abstract: Objective: There is a major unmet need for a molecular biomarker of seizures or epilepsy that lends itself to fast, affordable detection in an easy‐to‐use point‐of‐care device. Purines such as adenosine triphosphate and adenosine are potent neuromodulators released during excessive neuronal activity that are also present in biofluids. Their biomarker potential for seizures and epilepsy in peripheral blood has, however, not yet been investigated. The aim of the present study was to determine whether blood purine nucleoside measurements can serve as a biomarker for the recent occurrence of seizures and to support the diagnosis of epilepsy. Methods: Blood purine concentrations were measured via a point‐of‐care diagnostic technology based on the summated electrochemical detection of adenosine and adenosine breakdown products (inosine, hypoxanthine, and xanthine; SMARTChip). Measurements of blood purine concentrations were carried out using samples from mice subjected to intra‐amygdala kainic acid‐induced status epilepticus and in video‐electroencephalogram (EEG)‐monitored adult patients with epilepsy. Results: In mice, blood purine concentrations were rapidly increased approximately two‐ to threefold after status epilepticus (2.32 ± .40 µmol·L –1 [control] vs. 8.93 ± 1.03 µmol·L –1 [after status epilepticus]), and levels correlated with seizure burden and postseizure neurodegeneration in the hippocampus. Blood purine concentrations were also elevated in patients with video‐EEG‐diagnosed epilepsy (2.39 ± .34 µmol·L –1 [control, n  = 13] vs. 4.35 ± .38 µmol·L –1 [epilepsy, n  = 26]). Significance: Our data provide proof of concept that the measurement of blood purine concentrations may offer a rapid, low‐volume bedside test to support the diagnosis of seizures and epilepsy.